Uma análise de História Militar Comparada entre a Batalha de Memphis e Batalha de Riachuelo - Ricardo Pereira Cabral (Navigator)
This article intends to make a comparative analysis between two river battles that took place in the American Civil War and in the War of the Triple Alliance, namely the Battle of Memphis and the Battle of Riachuelo, highlighting the convergence of strategies, tactics and naval use.